Percepção de avicultores sobre aspectos tecnológicos, de biossegurança e exigências ambientais - Roman, Elias Turmena (My University, 2023)
Broiler farming is increasingly important in the national economy, surpassing the production of beef and pork both nationally and globally. Brazil stands out as the second largest chicken producer in the world and the largest exporter, competing with the United States and the European Union. Understanding the perception of poultry farmers in relation to technological aspects, biosafety and environmental demands, as well as their intention to continue and expand their activities based on the profitability obtained, is fundamental to understanding the sector. To achieve this purpose, a data collection instrument was developed and validated, collecting information from 50 poultry farmers in the municipalities of Vista Alegre do Prata - RS and Guaporé - RS. Descriptive statistics, analysis of variance (ANOVA) and Pearson correlation were used to analyze the data. The research developed in this work is classified in terms of approach as predominantly quantitative; in relation to nature, as applied; in relation to the objective, as exploratory-descriptive, and in relation to the research method, as a survey. Regarding technological aspects, the results show that poultry farmers who employ a higher level of technology have better economic results, whereas poultry farmers who employ a lower level of technology have the economic performance of their properties negatively affected. Furthermore, it was observed that factors such as the nature of the company, the size of the properties and the geographic location influence the different perspectives of the participants. This study is relevant, as it deepens the understanding of poultry farmers' perceptions regarding meat poultry farming and the main barriers faced, providing the formulation of practical solutions. Furthermore, this research offers valuable inputs for large integrator companies, such as JBS and BRF, in order to promote the efficiency of poultry farming in partnership with their integrated producers, while also pointing to opportunities for intervention by public authorities, particularly in municipal level. The results of this research also represent an important source of information, so that poultry farmers can invest and take actions, with the aim of increasing their financial gains, through understanding the impact of technological factors, biosafety and environmental requirements observed in poultry farms of different sizes. Certainly, it is worth mentioning that, based on the results of this research, a brochure has been developed for dissemination among producers, integrators, and municipal public administrations, indicating the potential and main difficulties in the area. [resumo fornecido pelo autor]
A avicultura de corte assume crescente relevância na economia nacional, superando a produção de carne bovina e suína tanto a nível nacional como global. O Brasil se destaca como o segundo maior produtor de frangos no mundo e o maior exportador, competindo com os Estados Unidos e a União Europeia. Compreender a percepção dos avicultores em relação a aspectos tecnológicos, biossegurança e demandas ambientais, bem como sua intenção de continuar e expandir suas atividades com base na lucratividade obtida, é fundamental para o entendimento do setor. Para alcançar esse propósito, um instrumento de coleta de dados foi desenvolvido e validado, com a coleta de informações de 50 avicultores nos municípios de Vista Alegre do Prata - RS e Guaporé - RS. Para análise dos dados foi empregado estatística descritiva, análise de variância (ANOVA) e correlação de Pearson. A pesquisa desenvolvida neste trabalho classifica-se, quanto à abordagem, como predominantemente quantitativa; em relação à natureza, como aplicada; em relação ao objetivo, como exploratório-descritiva, e em relação ao método de pesquisa, como survey. Em relação aos aspectos tecnológicos, os resultados demostram que os avicultores que empregam um maior nível de tecnologia, possuem melhores resultados econômicos, sendo que os avicultores que empregam um menor nível de tecnologia, possuem o desempenho econômico de suas propriedades afetado negativamente. Além disso, observou-se que fatores como a natureza da empresa, o tamanho das propriedades e a localização geográfica exercem influência nas diferentes perspectivas dos participantes. Este estudo se mostra relevante, uma vez que aprofunda o entendimento das percepções dos avicultores acerca da avicultura de corte e das principais barreiras enfrentadas, proporcionando a formulação de soluções práticas. Ademais, essa pesquisa oferece insumos valiosos para grandes empresas integradoras, como a JBS e BRF, a fim de fomentar a eficiência da avicultura de corte em parceria com seus produtores integrados, enquanto também aponta para oportunidades de intervenção por parte das autoridades públicas, particularmente em nível municipal. Ainda, os resultados desta pesquisa também representam uma importante fonte de informações para que avicultores possam investir e tomar ações, com objetivo de aumentar seus ganhos financeiros, por meio do entendimento do impacto dos fatores tecnológicos, de biossegurança e exigências ambientais observados em propriedades avícolas de diferentes portes. Dito isso, cabe mencionar que a partir dos resultados desta pesquisa foi produzido um encarte para ser divulgado junto a produtores, integradores e gestões públicas municipais, indicando os potencializadores e principais dificuldades da área. [resumo fornecido pelo autor]
Keywords: Indústria avícola; Percepção; Tecnologia; Biossegurança; Frango de corte; Licenças ambientais; Poultry industry; Perception; Technology; Biosafety; Broilers (Powltry); Environmental permits